Cloning and physical mapping of the cysB region of Salmonella typhimurium. - Jagura-Burdzy, G (1983)
The cysB region of Salmonella typhimurium was cloned in pBR322 and localized to a 1.75-kilobase HincII fragment. Two-dimensional protein electropherograms showed levels of the cysB polypeptide chain that were several fold higher in plasmid-bearing strains than in the wild type. Fully derepressed levels of sulfite reductase and O-acetylserine sulfhydrylase in cysB plasmid-bearing strains were only 25% higher than in the wild type, suggesting that the product of this regulatory gene ordinarily is not a limiting factor in the expression of the cysteine regulon. The mapping of cysB deletions by Southern blots showed a good correlation between the genetic and the physical maps of this gene. The supX gene was initially cloned with cysB and is within 0.7 kilobase of cysB.